Inter‐observer agreement for diagnostic classification of esophageal motility disorders defined in high‐resolution manometry. Issue 8 (3rd September 2014) - Fox, M. R.; Pandolfino, J. E.; Sweis, R.; Sauter, M.; Abreu Y Abreu, A. T.; Anggiansah, A.; Bogte, A.; Bredenoord, A. J.; Dengler, W.; Elvevi, A.; Fruehauf, H.; Gellersen, S.; et al.
Summary: High‐resolution esophageal manometry (HRM) is a recent development used in the evaluation of esophageal function. Our aim was to assess the inter‐observer agreement for diagnosis of esophageal motility disorders using this technology. Practitioners registered on the HRM Working Group website were invited to review and classify (i) 147 individual water swallows and (ii) 40 diagnostic studies comprising 10 swallows using a drop‐down menu that followed the Chicago Classification system. Data were presented using a standardized format with pressure contours without a summary of HRM metrics. The sequence of swallows was fixed for each user but randomized between users to avoid sequence bias. Participants were blinded to other entries. (i) Individual swallows were assessed by 18 practitioners (13 institutions). Consensus agreement (≤2/18 dissenters) was present for most cases of normal peristalsis and achalasia but not for cases of peristaltic dysmotility. (ii) Diagnostic studies were assessed by 36 practitioners (28 institutions). Overall inter‐observer agreement was 'moderate' (kappa 0.51) being 'substantial' (kappa > 0.7) for achalasia type I/II and no lower than 'fair–moderate' (kappa >0.34) for any diagnosis. Overall agreement was somewhat higher among those that had performed >400 studies ( n = 9; kappa 0.55) and 'substantial' among experts involved in development of the Chicago Classification system ( n = 4; kappa 0.66). This prospective, randomized, and blinded study reports an acceptable level of inter‐observer agreement for HRM diagnoses across the full spectrum of esophageal motility disorders for a large group of clinicians working in a range of medical institutions. Suboptimal agreement for diagnosis of peristaltic motility disorders highlights contribution of objective HRM metrics.